Selection of Reference Genes for RT-qPCR Analysis Under Extrinsic Conditions in the Hawthorn Spider Mite, Amphitetranychus viennensis - Yang, Jing; Zhang, Yuying; Zhao, Jin; Gao, Yue; Liu, Zhongfang; Zhang, Pengjiu; Fan, Jianbin; Zhou, Xuguo; Fan, Renjun (Frontiers in Physiology, 2020)
Hawthorn spider mite, Amphitetranychus viennensis Zacher, is an economically important arthropod pest for fruit trees and woody ornamental plants. Extensive and repetitive use of synthetic acaricides has led to the development of resistance in A. viennensis. To understand the molecular basis of pesticide resistance, and to develop genetic-based control alternatives (e.g., RNAi-based biopesticides), a standardized protocol for Real-Time Quantitative Reverse Transcription PCR (RT-qPCR) is needed. In the proceeding phase of this research, we screened for the internal references for RT-qPCR analysis from a pool of A. viennensis housekeeping genes under the intrinsic conditions, including developmental stage, sex, and diapause. Here, we continued our efforts to search for the reference genes under an array of extrinsic conditions, including temperature, humidity, photoperiod, host plant, and dietary RNAi. The stability of these candidate reference genes was investigated using geNorm, Normfinder, BestKeeper, and ΔCt method, respectively. Finally, RefFinder, a statistical platform integrating all four algorisms, provided a comprehensive list of genes for each extrinsic condition: 1) EF1A, α-tubulin and Actin3 were the best candidates for temperature, 2) GAPDH, 18S, and Actin3 were the most stable genes for humidity, 3) V-ATPase B, Actin3, and 18S were the top reference genes for photoperiod, 4) GAPDH, V-ATPase B, and α-tubulin were recommended for host plants, and 5) GAPDH, V-ATPase B, and RPS9 were the top choices for dietary RNAi. Overall, V-ATPase B, GAPDH, and Actin3 were the most commonly selected reference genes in A. viennensis regardless of the experimental conditions, including both intrinsic and extrinsic. Information present here lays the foundation for the genomic and functional genomic research in A. viennensis.